Wrack and ruin: Legacy hydrologic effects of hurricane-deposited wrack on hardwood-hammock coastal islands. (3rd June 2020) - Van Stan, John T; Allen, Scott T; Swanson, Travis; Skinner, Melissa; Gordon, D Alex
Abstract: Hurricanes can cause immediate catastrophic destruction of marsh vegetation and erosion of soils; however, they also have long-lasting ecological impacts. Those impacts include the deposition of tremendous amounts of saltmarsh litter ('wrack') onto upland ecosystems, the hydrologic effects of which have not previously been investigated. When Hurricane Irma battered the southeastern US coastline, widespread wrack deposition was reported (often exceeding 0.5 m depth), especially in vulnerable coastal hammock ecosystems: locally-elevated forests within the saltmarshes that rely on freshwater inputs from rain. We report the impacts of this deposited wrack, which has persisted for 2 years, on effective precipitation inputs to coastal hammock soils. At a coastal hammock site, wrack deposits of 22–38 cm depth were estimated to store 10.2–19.9 mm of rain, reducing net rainfall to the surface by 66% over the study period (Oct 2018– Jun 2019). Three months of calibration data collected from wrack lysimeters in the field supported this interception estimate, as only 49 mm of the total 170 mm (29%) of rain that fell on the wrack was transmitted through to the soil surface. These litter interception effects on precipitation inputs far exceed those that have been described in other ecosystems and we hypothesized that they alter the growing conditions of these precipitation-dependent trees. The marshgrass ( Spartina alterniflora ), from which the wrack that was studied originates, is a globally abundant native and often invasive plant; thus, understanding the duration and extent of those effects on ecohydrological processes may be crucial to managing and conserving these ecosystems, especially given rising sea levels and changing hurricane regimes.